THE INFLUENCE OF SERVICE QUALITY, WORD OF MOUTH, AND BRAND IMAGE ON LOYALTY WITH IBRAHIMY SITUBONDO UNIVERSITY STUDENT SATISFACTION MEDIATION - Moch. Syafi'i; Diah Yulisetiarini; Hari Sukarno (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2024)
This research aims to determine the influence of quality of service, Word of Mouth, and brand image on student loyalty by mediating student satisfaction at Ibrahimy Situbondo University. This study utilizes a research methodology. This study's population consists of active Ibrahimy University students. The method used in this study is Stratified Random Sampling. This study's sample size was 10 × 17 = 170 respondents. The data analysis method used path analysis with the SmartPLS 4 application. Research results show that (1) Service Quality to satisfaction shows a significant positive impact; (2) Word Of Mouth to Satisfaction shows significant positive effects; (3) Brand Image to satisfaction shows significant adverse effects; (4) Quality Service to Loyalty shows significant positives; (5) Word Of Mouth for loyalty shows a substantial positive effect; (6) Image of Brand to loyalty shows a considerable positive impact; (7) Satisfacy to Lojality shows an essential positive impact; (8) Quality of Services to Loiality through Satisface shows a meaningful positive effect; and (9) Word Of Mouth to Lioity through satisfaction indicates a significant negative impact.